Use of ripening fruits in seed production of early-maturing varieties of melons and gourds in spring and summer sowing - V. Е. Lazko; O. V. Yakimova; E. N. Blagorodova (Овощи России)
Relevance. In recent years, the price of seeds for melons and gourds of foreign selection has reoriented many agricultural producers to use seeds of domestic varieties. To provide agricultural producers with the required amount of seeds with high sowing rates, it is necessary to apply new technological methods that will allow using the biological potential of varieties and growing commercial volumes of seeds.Material and methods. The research was carried out at the selection and experimental site of the vegetable growing department in the "Federal Scientific Rice Centre " in 2017-2018. The object of research is a new promising variety of watermelon Yubilyar, and two early-ripening varieties of melon Tamanskay and Strelchanka. Sowing terms: spring – from mid-April to the end of the first decade of May, summer – the first and second decades of July. Summer sowing with drip irrigation. When harvesting melon and watermelon fruits, the selection intensity is 90% to obtain reproductive seeds RS-1.Results. It has been established that due to the climatic conditions of the Krasnodar Territory and the varietal characteristics of the melon varieties Tamanskaya, Strelchanka and the watermelon Yubilyar, a short growing season and a neutral reaction to changes in the length of the day, you can get two harvests of seeds in one season using summer sowing. It was noted that low air humidity prevented damage to plants by peronospora, anthracnose and powdery mildew, practically eliminating the need for protective measures. The selected ripe fruits for the selection of seeds by morphological characteristics corresponded to varietal characteristics. It has been established that the seed productivity of melon during summer sowing is higher due to better pollination. From one hectare received up to 97-138 kg of seeds. The use of ripening made it possible to carry out a one-time collection of watermelon and melon fruits.